Criminal Liability For Perpetrators For Mob Attack And Violations Of Public Order In Mekarjaya Village, Bogor Regency (Study In Cibinong State Court) - Chaerunnisa, Noer Samantha; Hartini, Sri; Iman Ferrary, Ande Aditya (JURNAL MAHASISWA YUSTISI, 2024)
The rampant cases of mob violence that occur in Indonesia, especially in the West Java region with a special scope of the Bogor area, both city and district, are currently being highlighted by the public. This can be caused by many factors, and often causes minor or serious injuries to victims of mob violence, therefore accountability is needed from the perpetrators before the law. With the existence of legal accountability that can prosecute perpetrators of criminal acts, especially violence and joint abuse in the form of mob violence, it is related to this that a lot of awareness is needed for the general public regarding the importance of maintaining public order. The purpose of writing this thesis is to find out the legal clarity obtained as a form of accountability from the perpetrators and to analyze what efforts the victims have made to strengthen evidence of the consequences of the mob violence in court. The method used by the author in writing this thesis is qualitative, carried out by collecting and analyzing data based on Decision No. 67 / Pid.B / 2022 / PN Cbi and processing it into a study and writing a thesis. The results obtained from writing this thesis are the results of the Visum Et Repertum on the victim of the assault in accordance with the Visum Et Repertum examination No. E 0094 / Sekr / XI / 2021